Reason of Intermediate Casing Wear in Ultra-deep Wells in China's Tarim Oil Field. (September 2020) - Ma, Chao; Gao, Baokui; Wang, Jieli; Hu, Tianxiang; Chen, Xingwang
Abstract: The intermediate casing wear is often found in ultra-deep wells in Tarim area. This phenomenon usually leads to many troubles in following well construction. By investigating 9 wells in this area that have severe intermediate casing wear, it is found that all casings are badly cemented, and the reason of casing wear is supposed to be helical buckling of casing string. In order to verify this judgment, geometry relationship among enlarged wellbore, buckled casing string and drill pipe joint are studied. When helical buckling occurs in casing string, apparent inner diameter of casing is usually smaller than the outer diameter of drill pipe joint. Therefore, rotating drill pipe joints wear casing inner surface continuously and forms a spiral scratch. Key factors that affect casing wear, such as wellbore enlargement rate, casing dimensions, casing centralizer and diameter of drill pipe joint, are discussed.